Cruising the Library: Perversities in the Organization of Knowledge - Adler, Melissa (Fordham University Press, 2017)
Cruising the Library examines the ways in which library classifications have organized sexuality and sexual perversion. The author studies the Library of Congress Subject Headings and Classification, as well as the Library of Congress's Delta Collection, a restricted collection of obscenity until 1964.